1996
DOI: 10.1038/ki.1996.292
|View full text |Cite
|
Sign up to set email alerts
|

rHuEPO enhances the production of plasminogen activator inhibitor-1 in cultured endothelial cells

Abstract: The direct effects of recombinant human erythropoietin(rHuEPO) on coagulation and fibrinolysis factors were evaluated in a cultured endothelial cell (EC) system. Confluent quiescent ECs were incubated with or without 5.0 U/ml rHuEPO for 1, 6, and 18 hours, and supernatant concentrations of plasminogen activator inhibitor-1 (PAI-1): antigen (Ag), tissue plasminogen activator and thrombomodulin, and supernatant activities of tissue factor pathway inhibitor and von Willebrand factor were measured. The results sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…Finally, plasminogen activator inhibitor-1 gene expression was determined, because even a short time of exposure to EPO is known to increase the production of plasminogen activator inhibitor-1 in endothelial cells (32). In this study, EPO and cEPO administration had no effects on heme oxygenase-1 and plasminogen activator inhibitor-1 gene expression.…”
Section: Gene Expression In the Kidneymentioning
confidence: 99%
“…Finally, plasminogen activator inhibitor-1 gene expression was determined, because even a short time of exposure to EPO is known to increase the production of plasminogen activator inhibitor-1 in endothelial cells (32). In this study, EPO and cEPO administration had no effects on heme oxygenase-1 and plasminogen activator inhibitor-1 gene expression.…”
Section: Gene Expression In the Kidneymentioning
confidence: 99%
“…Motor neuron function, however, did not recover, most likely due to the low dose of rhEPO administered and/or as a result of the marked tissue damage [4]. Moreover, Ehrenreich et al [5] recently reported a significantly higher overall death rate in rhEPO-treated patients with stroke, possibly as a result of the high number of patients undergoing systemic thrombolysis with recombinant tissue plasminogen activator: in vitro, a single rhEPO exposure enhances production of plasminogen activator inhibitor-1 [6].…”
Section: Introductionmentioning
confidence: 99%
“…The calcium protein channels can also become phosphorylated during EPO-R mediated activation [22]. As well as being expressed on the erythroid precursors [23], EPO-R is also expressed on the megakaryocytes [24], VSMC [25,26], endothelial cells [26][27][28], skeletal myoblasts [29], neuronal [30] and renal cells [31].…”
Section: Epo Receptormentioning
confidence: 99%